Mediating effect of gastrointestinal symptoms on dietary behavior and quality of life in Chinese adults with chronic gastritis—a cross-sectional study - Zhao, Litong; Zhang, Feng; Kuang, Dan; Li, Dan; Yan, Jiai; Yang, Ju; Wang, Qinyue; Wang, Yingyu; Sun, Jing; Liu, Yiran; Liu, Ping; Xia, Yanping; et al. (Frontiers in Medicine, 2023)
Background: Chronic gastritis is accompanied by varying degrees of gastrointestinal symptoms, affecting people's quality of life. The association between dietary behaviors and gastrointestinal symptoms of patients with chronic gastritis has been proved recently. However, no studies have been conducted to investigate the relationship between dietary behaviors, gastrointestinal symptoms, and quality of life. Methods: A cross-sectional survey of 176 patients diagnosed with Chronic gastritis aged 18 to 65 years, and their information on demographic characteristics, dietary behaviors, gastrointestinal symptoms, and quality of life was collected. A descriptive analysis and a correlation matrix were used to illuminate the characteristics of the subject and bivariate correlation, respectively.The mediation model was analyzed using the PROCESS macros for SPSS. Results: Demographic characteristics influence the symptoms, dietary behaviors, and quality of life of chronic gastritis patients, in particular, students categorized by occupation, had higher levels of gastrointestinal symptoms and lower levels of quality of life and dietary behavior. The study variables were all pound-related. We found that gastrointestinal symptoms played a partial mediating role between